Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s0002-9270(03)00133-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone density in a population-based cohort of premenopausal adult women with early onset inflammatory bowel disease

Abstract: OBJECTIVE:We aimed to determine the bone mineral density (BMD) using dual energy x-ray absorptiometry in a population-based sample of women with inflammatory bowel disease who were diagnosed before age 20 yr and who are currently premenopausal and less than 45 yr. METHODS:The University of Manitoba Inflammatory Bowel Disease Epidemiology Research Registry was accessed to find eligible women. Of 171 eligible subjects, 82 agreed to participate, and 70 appeared for dual energy x-ray absorptiometry. All subjects c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 28 publications
0
12
0
2
Order By: Relevance
“…Osteopenia (also called low bone mass) has been reported in patients with chronic inflammatory diseases such as chronic periodontitis [1] and pancreatitis [2], inflammatory bowel disease [3], rheumatorid arthritis [4], and lupus erythematosus [5]. The pathogenesis of low bone mass in patients with such chronic inflammatory diseases is complex.…”
Section: Introductionmentioning
confidence: 99%
“…Osteopenia (also called low bone mass) has been reported in patients with chronic inflammatory diseases such as chronic periodontitis [1] and pancreatitis [2], inflammatory bowel disease [3], rheumatorid arthritis [4], and lupus erythematosus [5]. The pathogenesis of low bone mass in patients with such chronic inflammatory diseases is complex.…”
Section: Introductionmentioning
confidence: 99%
“…[38] Chronic inflammation and increased pro-inflammatory cytokines TNF-α and IL-6 induce bone resorption and bone loss in a number of diseases, such as periodontitis, [39] rheumatoid arthritis, [40] and inflammatory bowel disease. [41] These pro-inflammatory cytokines in obesity stimulates osteoclastactivity and bone resorption through RANKL/RANK/OPG pathways. [79] In this study, serum levels of chemerin, as well as TNF-α, were negatively associated with BMD measurements of the lumbar spine in obese population, which is in line with the study by He et al, [42] who also found negative effect of chemerin on BMD in osteoporotic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic inflammation and increased proinflammatory cytokines induce bone resorption and bone loss in patients with periodontitis (Van Dyke and Serhan, 2003), pancreatitis (Mann et al, 2003), inflammatory bowel disease (Bernstein et al, 2003), and rheumatoid arthritis (Romas et al, 2002). It has also been established that upregulated proinflammatory cytokines are primary mediators of osteopenia or osteoporosis.…”
Section: Biologic Mechanisms For the Bone-fat Connectionmentioning
confidence: 99%